2011
DOI: 10.1007/s12011-010-8951-3
|View full text |Cite
|
Sign up to set email alerts
|

Selenium–Vitamin E Combination and Melatonin Modulates Diabetes-Induced Blood Oxidative Damage and Fetal Outcomes in Pregnant Rats

Abstract: Oxidative stress is considered to be the main cause of diabetic complications. In the current study, we investigated the effect of selenium-vitamin E combination and melatonin on lipid peroxidation (LPO) and scavenging enzyme activity in the blood of streptozocin (STZ)-induced diabetic pregnant rats. Forty female Wistar rats were randomly divided into five groups. The first and second groups were used as the non-pregnant control and pregnant control groups, respectively. The third group was the pregnant diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…Studies have shown that selenium can protect against oxidative damage attributable to unregulated blood sugar [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that selenium can protect against oxidative damage attributable to unregulated blood sugar [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Many diabetic complications are thought to be caused by oxidative damage and decreased antioxidant protection. For example, studies have shown that selenium can protect against oxidative damage attributable to unregulated blood sugar [98,99]. In one animal study, hamsters fed a low selenium diet had diabetes-induced weight loss, increased plasma triglyceride and cholesterol concentrations and rapid oxidation of LDL, none of which were seen in hamsters fed a high selenium diet [100].…”
Section: Type 2 Diabetes and Seleniummentioning
confidence: 99%
“…Previous studies have demonstrated α-T efficacy against HP-induced oxidative stress on different cell types, such as astrocytes, placental cells, fibroblasts and hepatocytes (13,14). Additionally, α-T increases the expression of endogenous antioxidants, such as dismutase superoxide and catalase (15)(16)(17), and reduces gene expression of inflammatory mediators (9). In this way, α-T has an effective role in antioxidant and antiinflammatory events (24).…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, it is known that the antioxidant action of VE is mediated by its alpha-tocopherol (α-T) isomer, which has the capacity to incorporate to the cell membrane and stop lipid peroxidation propagation (11). Several researchers have assessed the protective effect of α-T and confirmed its capacity to prevent oxidative stress propagation, stabilize the cell membrane, enhance cell viability and increase the amount of endogenous antioxidants (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%